PENDAMPINGAN PROSES PEMBELAJARAN LURING SISWA MADRASAH IBTIDAIYAH MELALUI MODEL PEMBELAJARAN SCIENTIFIC LEARNING DESA KARANGSARI BANYUWANGI PADA ERA COVID-19 - Ahmad Izza Muttaqin; Anis Fauzi; Al Muftiyah; Tamara Bunga Velia (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
Learning is a process of interaction between students, educators and learning resources and evaluation to achieve the learning process. Community service is realized in the form of mentoring student learning processes from home. Offline learning is a form of learning that is not at all connected to the internet. Offline learning is the opposite of darling learning. Meanwhile, Scientific learning is an approach used in learning with a focus on the use of scientific methods in the learning process. The subject is a student of MI Darul Ulum class V and parents of students. Aiming to overcome the problem of student learning at home during the darling Covid-19 period. Some of the program activities undertaken are as follows: a) Offline Learning Process at Home b) Learning Assistance with Scientific Learning Approach.